Adopting Geo-ICT in Survey Department: Need for Capacity Building - Shrestha, Kalyan Gopal (Journal on Geoinformatics, Nepal, 2010)
The Geospatial Information and Communication Technology (Geo-ICT), is gaining momentum and has revolutionized the Surveying and Mapping profession. Since the geo-technology is evolving continuously, constant efforts are being made for its diverse applications. Most of the users are convinced that digital technology is known for its easy use and the power to improve their work process. Survey Department has witnessed tremendous changes in the technologies and corresponding policies in Global scenario in last fifty two years of its history and particularly during last two decades. Adoption of Geo- ICT has become indispensable in the present context. Even though Survey Department, so far, is not in the stage of fully exploiting the Geo-ICT, Time has come to think of adopting Geo-ICT application. Because, the wider use of Geo-ICT could be prime instrumental to support the overall Surveying and Mapping business. The success of efficient Geo-ICT application heavily depends on the capacity building, institutional reforms, devolution, education and continuous training, and ultimately the commitment of the government. This article has tried to focus on various factors responsible for successful implementation of Geo-ICT in Nepalese context.